Peroxymonosulfate activation on carbon nano-onions modified graphitic carbon nitride via light-tuning radical and nonradical pathways. Issue 6 (December 2021) - Jiang, Qiongji; Gan, Huihui; Huang, Yin; Lu, Dingnan; Yang, Yanqing; Zhang, Weike
Abstract: Carbon-based catalyst has unique advantages as peroxymonosulfate (PMS) activator due to its unique structure and metal-free characteristics. Herein, the carbon nano-onions modified graphitic carbon nitride (CN-CNO) were prepared via the facile ultrasonic-assisted method in different proportions. With the aid of visible-light, the CN-CNO catalyst possessed a much better PMS activation capacity for norfloxacin (NOR) degradation than conventional C3 N4 . The incorporation of CNO with g-C3 N4 provided an effective interface afforded by the π-π stacking interaction, which significantly enhanced photogenerated-electron mobility as evidenced by electron microscopy and electrochemical studies. Radical quenching experiments and EPR illustrated that the outstanding oxidative performance of CN-CNO/PMS system originated from the h +, O2 -, SO4 -, OH and 1 O2 under visible-light irradiation. In addition, in the absence of light, CN-CNO/PMS system exhibited nonradical degradation for NOR through the possible surface-bound complexes mediated electron transfer pathway, confirmed by radical scavenging, substrate specificity test and ATR-FTIR spectra. According to the NOR degradation path analysis, complete intermediates were detected under visible light. This study supplies new insight into the fabrication and application of carbon-based catalysts for efficient antibiotic pollution elimination in aquatic environments. Graphical Abstract: ga1 Highlights: NOR was degraded effectively by CN-CNO activating PMS. The incorporation CNO could promote effective charge transfer in two systems. The mechanisms for NOR degradation involved the surface electron transfer and the formation of ROS. Degradation products of NOR by the CN-CNO-2/vis/PMS system were identified.